Evaluation of the image quality by using MEGP and HEGP collimators for Iodine-131 in planar imaging - Jianan, Ding (2024)
Purpose: High-energy general-purpose (HEGP) collimators are mostly used for iodine- 131 in SPECT and planar imaging, while medium-energy general-purpose (MEGP) collimators are seldom used due to the high radiation of iodine-131. In this study, we evaluated the image quality by using MEGP and HEGP collimators with different activities of iodine-131 in planar imaging. Aspects of image quality evaluated include sensitivity, contrast, signal-to-noise ratio, and resolution. Materials and methods: To scan the iodine-131 in several activities, three petri dishes were used to contain iodine-131. Each petri dish contained 0.2 mCi, 0.4 mCi, and 0.6 mCi of iodine-131, and saline was also added to the petri dish. The planar technique produces static images of petri dishes with iodine-131 from two detectors, and then the information about the petri dishes and background were measured in Xeleris workstation. Based on the specific formulas, sensitivity, contrast, SNR, and resolution were calculated. Results: Sensitivity in the MEGP collimator is higher than that in the HEGP collimator, while SNR for the HEGP collimator is higher than that in the MEGP collimator. As for resolution and contrast, the MEGP and HEGP collimators show almost similar but still slightly different results in the generated images. Conclusion: All in all, MEGP and HEGP collimators have their own strengths in image quality using low-activity of iodine-131. Sensitivity in the MEGP collimator is better, and SNR in the HEGP collimator is better.